Analisis Komparatif Kinerja pada Lembaga Perkreditan Desa Kecamatan Mengwi dengan Metode Balanced Scorecard - Setia Dewi, I Gusti Ayu Agung Meilinda; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 23 No 1 (2018), 2018)
This study aims to determine the differences in the of LPD in Mengwi district by balanced scorecard method used 20 LPD samples using proportionate stratified random sampling method. Performance appraisal from financial perspective is measured by ROI ratio, customer perspective measured by customer satisfaction level, internal business process and growth and learning measured by employee satisfaction level, respresent in this research are 75 LPD employees and 100 LPD customers taken using simple random sampling. Hypothesis testing in this research using ANOVA test. This research is expected to implies the stakeholders such as LPD employees, LPD customers, and steward of LPDs. Based on the results of the analysis there are differences in performance in LPD Mengwi district from financial perspective, customer perspective, internal business process perspective, and growth and learning perspective.